Diversity and Inclusion: Are We Nearly There Yet?: Target Setting in the Screen Industries - Doris Ruth Eikhof (Routledge, 2024)
This book provides the first compact knowledge base on diversity & inclusion (D&I) targets in the UK screen industries. Drawing on new, in-depth industry research and progressive theoretical voices, the book will help readers understand what D&I targets are and what they could be in the future. The book explains different types of D&I targets, how D&I targets are currently used and how they might be developed to strategically drive inclusion. D&I targets are an increasingly common feature of the screen industries, but there is little evidence and guidance on how to use them well. This book addresses that gap. The book offers, for the first time, a unifying terminology for D&I target setting in the UK screen industries, including for transorganisational D&I targets (targets set by one organisation for another). It is based on a cross-industry review of D&I target setting in the UK screen industries, using evidence from industry and academic research. Providing a unique knowledge base on diversity & inclusion targets in the UK screen industries, this book will be of value to researchers, industry experts, practitioners, policy makers, campaigners and anyone who needs to understand D&I targets – to advise on them, to set and achieve them and to advocate for their effective, inclusive use.
Keywords: 790; big screen; creative industries; cultural industries; demographic data; equality; film industry; monitoring; television